# If f(x) = x2 + 9x – 6, then let us write by calculating the values of f(0), f(1) and f(3).

Formula used/Theory.

Putting the value of ‘x’ in f(x) gives out the value of f(x) on ‘x’

We have,

f(x) = x2 + 9x – 6

When we put

x = 0

Then,

f(0) = 02 + 9 × 0 – 6

f(0) = –6

when we put

x = 1

Then,

f(1) = 12 + 9 × 1 – 6

f(1) = 10 –6

f(1) = 4

When we put

x = 3

Then,

f(3) = 32 + 9 × 3 – 6

f(3) = 9+27 –6

f(3) = 30

Conclusion.

The values of f(0), f(1), f(3) are –6, 4, 30 respectively.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Polynomial Identities31 mins
Zeros and Degrees of a Polynomial41 mins
Polynomial Identities in a Different Way43 mins
Methods to find zeroes of a polynomial 139 mins
Methods to find zeroes of a Polynomial-246 mins
How to avoid Polynomial Long Division when finding factors.40 mins
Concept of Zero & Degree of a Polynomial.54 mins
Champ Quiz | Geometrical Meaning of the Zeroes of a Polynomial38 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses